LAKU HIDUP BAHAGIA: STUDI KOMPARATIF FILSAFAT YOGA DAN STOIKISME - Juniartha, Made G.; Anjani, Ni Ketut (Sanjiwani: Jurnal Filsafat, 2024)
This article discusses the comparison of two ancient philosophies, Yoga and Stoicism, in terms of how these two defines happiness and offers a guide to achieving it. Yoga, originally from India, focuses on the unification of body, mind, and soul through sadhana aṣṭāṅgayoga. Stoicism, originating in Greece, emphasizes the importance of virtue and self-control in achieving inner peace. Although different in origin and approach, these two philosophies have much in common in terms of purpose. Both Yoga and Stoicism offer a path to happiness that does not depend on external circumstances, but on internal changes in the way we think, say and act. This article compares and analyzes key concepts in both philosophies, such as virtue, self-control, and inner peace. Through this research, it shows that the philosophy of Yoga and Stoicism can offer useful strategies for individuals seeking happiness and meaning in life. This research uses qualitative methods with library-based research.